1997
DOI: 10.1073/pnas.94.26.14742
|View full text |Cite
|
Sign up to set email alerts
|

CD4-independent, CCR5-dependent infection of brain capillary endothelial cells by a neurovirulent simian immunodeficiency virus strain

Abstract: Brain capillary endothelial cells (BCECs) are targets of CD4-independent infection by HIV-1 and simian immunodeficiency virus (SIV) strains in vitro and in vivo. Infection of BCECs may provide a portal of entry for the virus into the central nervous system and could disrupt blood-brain barrier function, contributing to the development of AIDS dementia. We found that rhesus macaque BCECs express chemokine receptors involved in HIV and SIV entry including CCR5, CCR3, CXCR4, and STRL33, but not CCR2b, GPR1, or GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
198
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 34 publications
10
198
1
Order By: Relevance
“…As previously reported, we found that BMECs lack the entry receptor CD4 as well as GalCer ( Fig. 1A and B) (23,54). We also found that BMECs express low levels of both coreceptors CCR5 and CXCR4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 69%
See 2 more Smart Citations
“…As previously reported, we found that BMECs lack the entry receptor CD4 as well as GalCer ( Fig. 1A and B) (23,54). We also found that BMECs express low levels of both coreceptors CCR5 and CXCR4 ( Fig.…”
Section: Cell Surface Expression Of Proteoglycans On Primary Humansupporting
confidence: 69%
“…Lastly, anti-CD4 antibodies (SIM2 and SIM.4) (100 l of culture supernatant per ml of each) failed to prevent HIV-1 attachment, entry, and transcytosis (Fig. 6), further suggesting that HIV-1 crosses the BBB in a CD4-independent manner as proposed previously (23,54). Note that we verified the potency of these entry inhibitors (Fig.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The types of receptors engaged by Env and how Env engages those receptors are factors that can influence viral tropism and pathogenesis. Thus, viruses that evolve from using CCR5 to using CXCR4 appear to be less adept at establishing infections in new hosts but are associated with accelerated disease progression in those with established infections (15), while decreased dependence on CD4 levels has been linked to macrophage tropism in the simian immunodeficiency virus system and neurotropism for both simian immunodeficiency virus and HIV (4,22,26,41). Theoretically, how well an Env binds to a coreceptor and how Env responds to receptor binding could also influence tropism and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 is expressed on a number of hematopoietic cells, including lymphocytes, macrophages, and granulocytes, and also on non-hematopoietic cells [15][16][17][18]. CCR5 binds to multiple chemokines including CCL3, CCL4/ MIP-1b, and CCL5 [19,20].…”
Section: Introductionmentioning
confidence: 99%